Fabrication and characterization of copper (II) oxide/iron (III) oxide thin film heterostructures for trace arsenic (III) removal in water - Pastrana, Elizabeth C. (2021)
The work described in this paper was financially supported by the National Fund for the Scientific and Technological Development (FONDECYT), Grant No. 237–2015-FONDECYT. The authors thank Dr. Breno Pannia Espósito and the LABQAM of the Chemistry Institute of USP for the analysis of the samples. In addition, authors thank Dr. Pierre Ramos Apestegui for his excellent technical assistance with scanning electron microscopy observation.